The Influence of Perception of Justice on the Tendency of Students to Demonstrate - Nurdin, Muhammad Nur Hidayat; Piara, Muhrajan; Abrar, Khairunnisa Putri (PINISI Discretion Review, 2022)
This study aims to determine the role of perception of justice on the tendency of students in staging demonstration. Perception of justice is the perception of justice at Makassar State University which is reviewed based on three aspects, namely distributive, procedural, and interactional justice. The tendency of demonstrations is the tendency of Makassar State University students in carrying out mass protests. The method used in this research is survey method . The population in this study were Makassar State University students who joined students organizations. The results showed that the perception of justice did not significantly influence the tendency of students in staging demonstration behavior at the Makassar State University. Based on the descriptive analysis, there are 57% of respondents who do not to take part in the demonstration considering their beliefs, the inability of themselves and the environment that could not be controlled by the individual.